Prevalence and predictors of binge eating disorder symptoms among a sample of university students in Bangladesh: a cross-sectional survey - Abid, MT; Banna, MHA; Akter, S; Brazendale, K; Spence, C; Begum, MUH; Rashid, R; Bari, FS; Rifat, MA; Sultana, MS; Khaleduzzaman, M; Debnath, SC; et al. (Wiley, 2023)
Background and Aims: There is a dearth of information about binge eating disorder (BED) among Bangladeshi university students, who may be more susceptible to BED due to the rise in unhealthy lifestyles and food habits. Therefore, the purpose of this study was to assess the prevalence and associated factors of BED symptoms among Bangladeshi university students. Methods: Students (N = 525) from three public universities in Bangladesh participated in this cross-sectional study between November 2022 and March 2023. Face-to-face interviews were conducted using a structured paper-based questionnaire that included two validated survey tools; the binge eating disorder screener and the patient health questionnaire-9. To identify the factors associated with BED symptoms, multiple logistic regression analysis was conducted, with sociodemographic and behavioral information (e.g., age, sex, smoking status, etc.) considered as covariates. Results: The prevalence of BED symptoms among participants (mean age 21.28 years, 50.3% male and 49.7% female) was 20.6%. Male students had a 2.28 times higher likelihood of having BED symptoms compared to female counterparts (adjusted odds ratio [AOR] = 2.28; 95% CI: 1.33−3.89). Older students (AOR = 3.56, 95% CI: 1.80−7.05), students who were overweight or obese (AOR = 3.32, 95% CI: 1.87−5.89), and students reporting higher depressive symptoms (AOR = 2.69, 95% CI: 1.66−4.35) were at greater risk for developing BED compared to their respective counterparts. Conclusions: This study provides new insights into the prevalence of BED symptoms and its contributing factors among Bangladeshi students. Approximately 1-in-5 university students reported having BED symptoms. University students who are older, overweight, or obese, and who report depressive symptoms may be at greatest risk. Future longitudinal studies are needed to determine the causal factors underlying BED. Findings from this study can assist policymakers and public health professionals in developing effective and targeted strategies to mitigate the risks associated with BED among Bangladeshi university students.